Heparin-Free Lung Transplantation on Venovenous Extracorporeal Membrane Oxygenation Bridge. Issue 11 (1st February 2021) - Scaravilli, Vittorio; Fumagalli, Jacopo; Rosso, Lorenzo; Polli, Federico; Panigada, Mauro; Abbruzzese, Chiara; Crotti, Stefania; Lissoni, Alfredo; Nosotti, Mario; Pesenti, Antonio; Zanella, Alberto; Grasselli, Giacomo
Abstract : Supplemental Digital Content is available in the text. Abstract : Extracorporeal membrane oxygenation (ECMO) bridge to lung transplantation (LuTX) exposes the patients to a high risk of perioperative bleeding secondary to systemic anticoagulation and coagulation factors deficiency. With this case series, we propose innovative "no-heparin" management of ECMO-bridge support during LuTX, based upon 1) control heparin resistance with antithrombin III in the preoperative period; 2) relying upon a fully functional, brand new heparinized ECMO circuit; 3) completely avoiding perioperative heparin; 4) hampering fibrinolysis with tranexamic acid; and 5) limiting venoarterial (VA) ECMO escalation, and the following need for full anticoagulation. Following the application of this new approach, we carried out three challenging clinical cases of bilateral ECMO-bridged LuTX effectively, with limited intraoperative blood requirement and no major postoperative bleeding or thromboembolic events. Of note, two of them had an extremely high risk for hemorrhage due to complete right lung anatomic derangement in case number 2 and surgical adhesion following first LuTX in case number 3, while for the case number 1, no blood products were administered during surgery. Despite the limited patient population, such an approach relies on a strong rationale and may be beneficial for managing ECMO bridging to LuTX. Prospective studies are necessary to confirm the validity of our strategy.